A Review: Inflammatory Process in Alzheimer's Disease, Role of Cytokines - Jose Miguel Rubio-Perez; Juana Maria Morillas-Ruiz (The Scientific World Journal)
Alzheimer's disease (AD) is the most common neurodegenerative disorder to date. Neuropathological hallmarks are β-amyloid (Aβ) plaques and neurofibrillary tangles, but the inflammatory process has a fundamental role in the pathogenesis of AD. Inflammatory components related to AD neuroinflammation include brain cells such as microglia and astrocytes, the complement system, as well as cytokines and chemokines. Cytokines play a key role in inflammatory and anti-inflammatory processes in AD. An important factor in the onset of inflammatory process is the overexpression of interleukin (IL)-1, which produces many reactions in a vicious circle that cause dysfunction and neuronal death. Other important cytokines in neuroinflammation are IL-6 and tumor necrosis factor (TNF)-α. By contrast, other cytokines such as IL-1 receptor antagonist (IL-1ra), IL-4, IL-10, and transforming growth factor (TGF)-β can suppress both proinflammatory cytokine production and their action, subsequently protecting the brain. It has been observed in epidemiological studies that treatment with nonsteroidal anti-inflammatory drugs (NSAIDs) decreases the risk for developing AD. Unfortunately, clinical trials of NSAIDs in AD patients have not been very fruitful. Proinflammatory responses may be countered through polyphenols. Supplementation of these natural compounds may provide a new therapeutic line of approach to this brain disorder.